Encouraging Islamic Hospitality with Indigenization in Indonesia and Malaysia - Sholikhah, Ronaa Nisa'us (Advanced Studies on Socio-Economy Development, 2024)
Every society has struggled endlessly to maintain its identity since colonial times. One of them is the cultural concept of carrying out worship in a religion, which has been expanded massively through the cultivation of black-and-white ideology, right and wrong, or which means the truth of the teachings determines the obedience of religious people. However, this issue has become popular because many people want to be more compliant, so the migration movement is massive in society. This article examines that since Islamophobia emerged as a result of the 9/11 tragedy, Indonesia and Malaysia have conceptualized friendly Islam with the theme of religious moderation. This research uses a qualitative approach with the critical juncture method. Research findings show that in Malaysia, a multi-ethnic party won last year's elections after falling out with a Malay-Muslim party. Identity politics is quite strong in Indonesia. Meanwhile, Indonesia is busy promoting Wasatiyya Islam as a basic religion, and it was also promoted in the R20 last year. For years, these two countries have tried to become friendly countries for various ethnicities and religions. Thus, indigenization is more suitable because the two countries have similar traditions and cultures, so indigenization is important for politics and the state. Keywords: Indigenization, Religious Moderation, 9/11 Tragedy, and Political Identity